Ngurisan Tradition in the View of Buddhism - Munisah Munisah; Eko Prasetyo (Subhasita: Journal of Buddhist and Religious Studies, 2023)
The Ngurisan tradition is an ancestral heritage that is hereditary. The purpose of the Buddhist community carrying out the Ngurisan tradition is as a form of gratitude, thanks to parents for being blessed with a child and to pray for and cleanse the child from unwanted things. The problem to be studied is the implementation of the Buddhist Ngurisan tradition. The purpose of this research is to find out the process and meaning of Ngurisan tradition of Buddhist community in Mareje village, Lembar sub-district, West Lombok regency. This research was conducted on the Buddhist community in Mareje Village, Lembar District, West Lombok Regency. This research uses a qualitative approach, namely ethnographic study with data collection techniques including interviews, observation, and documentation. Ngurisan tradition is a celebration event in the form of a haircut tradition ceremony intended for children. The procession of the Ngurisan tradition includes activities (1) Family-level consensus (2) Bau Tomplak (taking materials) (3) Bait Jelo (determining a good day) (4) Jelo Gaur (The third day before the peak day of Ngurisan) (5) Jelo Naikan (the second day before the peak day). (6) Jelo gawe (peak day) and (7) Metun baok (activities after the event is over). The Ngurisan devotional ceremony uses offerings in the form of candles, incense, water, flowers, fruit, and food in the form of rice. The Ngurisan tradition means that children who have been drained can be given health, welfare, and in the future can live a life full of happiness. As for custom, it is an obedience or respect for the ancestors. A child has an obligation to be devoted to parents, maintain family honor and traditions, keep the inheritance well and pray for them when they have died. Religiously, it can be a way to deepen and increase faith (Saddha) for Buddhists. Buddhism also defines the Ngurisan tradition as a form of merit offering (patidana).